Pengaruh Roa, Dar, Cr Terhadap Financial Distress Pada Perusahaan Properti, Real Estate And Building Construction Yang Terdaftar Di Bei Tahun 2014-2018 - Ratnawati (Jurnal Ekonomi dan Bisnis Digital, 2023)
The purpose of this study was to determine the effect of ROA on Financial Distress in property, real estate and build construction companies for the period 2014-2018. This study was conducted to prove how the influence of ROA, DAR, and Current Ratio on financial distress within a period of five years (2014-2018). The object of research taken is property, real estate, and build construction companies listed on the Indonesia Stock Exchange (IDX) for the period (2014-2018). Based on the results of tests and discussions conducted by researchers regarding the effect of Return on Assets, Debt to Asset Ratio, Current Ratio on Financial Distress in Property, Real Estate And Building Construction Companies listed on the IDX in 2014-2018, it can be concluded that Return on Assets has a positive effect. and significant to Financial Distress in Property, Real Estate And Building Construction Companies listed on the IDX in 2014-2018. (Hypothesis 1 accepted)